The Validity of STEM-Based Digital Comic Media on the Topic of the Structure And Function of Human Respiration - Hasanah, Maisyatul; Hasbiyati, Haning; Hikamah, Siti Roudlotul (JIPVA (Jurnal Pendidikan IPA Veteran), 2024)
Learning media is anything that is capable of conveying a message, influencing the minds, emotions, and motivations of learners, thereby fostering the creation of the learning process within them. The results of interviews conducted with Natural Sciences (IPA) teachers at one of the MTs in Jember can be summarized as follows: the use of learning media is still not optimal, while the structure and function of the human respiratory system remain abstract and related to everyday life. This research aims to determine the validity of a STEM-based digital comic media with the subject of the structure and function of the human respiratory system. This study utilizes a research and development method with the Plomp development model, which consists of three stages: initial research, prototype development, and evaluation. The results of this development research obtained a score of 83.11%, categorized as highly valid for media validation, and 86.66%, categorized as highly valid for material validation. Based on the research results at the MTs, it can be concluded that the STEM-based digital comic media on the topic of the structure and function of the human respiratory system is valid for use